Consumer Satisfaction Analysis Towards Store Atmosphere And Location Using Importance-Performance Analysis - Farah Nur Fadhilah; Nurafni Rubiyanti (Politeknik APP Jakarta, 2024)
This study aims to analyze customer satisfaction with store atmosphere and location using Importance Performance Analysis (IPA). Sampling was done by using probability sampling technique used is judgment sampling with 100 consumer respondents who have visited and made purchases at Yugen Cafe. The results of the data from the distribution of the questionnaire were obtained using Gap analysis to determine the level of customer satisfaction and then retrieved using Important Performance Analysis (IPA) to find out which attributes need to be maintained by the company's performance. Based on the results of data processing, it can be seen that the customer's assessment of 30 performance attributes and 30 expectations attributes indicates that all attributes have a gap between customer perceptions of Yugen Cafe. Based on the level of conformity, the results obtained 95.1%, indicating that it is still below 100% and has not met customer expectations at Yugen café.